2015
DOI: 10.1016/j.foreco.2015.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Scarification and gap size have interacting effects on northern temperate seedling establishment

Abstract: a b s t r a c tAfter decades focused on promoting economically valuable species, management of northern temperate forests has increasingly become focused on promoting tree species diversity. Unfortunately, many formerly common species that could contribute to diversity including yellow birch (Betula alleghaniensis Britton.), paper birch (Betula papyrifera Marsh), eastern hemlock (Tsuga canadensis L.), and eastern white pine (Pinus strobus L.) are now uncommon in the seedling layer, raising concerns about our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 90 publications
0
17
0
Order By: Relevance
“…Similarly, Willis et al. () demonstrated interactions between canopy openness and scarification were critically important for tree establishment and coexistence in harvest gaps. These results suggest that a historical disturbance regime (i.e., windthrow) can promote coexistence, but only in combination with additional disturbances to the understory vegetation and soil (here, scarification caused by salvaging; see also Oliver and Larson , Roberts , ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Willis et al. () demonstrated interactions between canopy openness and scarification were critically important for tree establishment and coexistence in harvest gaps. These results suggest that a historical disturbance regime (i.e., windthrow) can promote coexistence, but only in combination with additional disturbances to the understory vegetation and soil (here, scarification caused by salvaging; see also Oliver and Larson , Roberts , ).…”
Section: Discussionmentioning
confidence: 88%
“…In sharp contrast, increasing canopy windthrow severity combined with scarification resulting from salvage logging enhanced the establishment of hardwood species of high economic value and promoted species coexistence. Similarly, Willis et al (2015) demonstrated interactions between canopy openness and scarification were critically important for tree establishment and tAble 3. Results of repeated measure analyses of covariance sapling richness, basal area, stem density, and diversity (H′).…”
Section: Salvaging and Windthrow Severity Interactions Enhance Speciementioning
confidence: 97%
“…Seedlings are often found over a range of substrates in the forest understory. In managed northern hardwood forest in the Lake States region, hardwood litter is the most common seedling establishment substrate (Willis et al 2015). Compared to other substrate types, hardwood litter may present a more imposing physical barrier for root radicle penetration, and resource availability may be more variable and limited as the most stable supply of moisture and mineral nutrients is contained in the underlying humus and mineral soil layers (Houle 1992, Prescott et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…), northern white cedar (Thuja occidentalis L.), and eastern hemlock (Tsuga canadensis L.), have less reserve energy available to allocate toward root development (Moles and Westoby 2004). Consequently, in northern hardwood forests, smaller-seeded species seedling establishment is often confined to mineral soil and heavily decayed, large pieces of coarse woody debris (CWD), where resources are more easily accessed and less variable (Cornett et al 2001, Shields et al 2007, Marx and Walters 2008, Bolton and D'Amato 2011, Willis et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Sapkota and Odén (2009) studied the effect of gap characteristics on woody species in a dry Shorea robusta forest, and the results indicated that Terminalia alata seedling density was significantly and positively correlated with gap area. Large gap size supplies a convenient environment for plant establishment, as noted in a study of seedling establishment in a northern temperate forest, where highest density of plant species in the seedling layer was found in large gap size (Willis et al 2015). The seedling and shrub stages of C. kawakamii preferred the environment in large gap size over small gap size.…”
Section: Gap Areas and Number Of Castanopsis Kawakamiimentioning
confidence: 84%